Creating Space Invaders, a 2D Based Game by Using HTML5 and Javascript - Nazar, Muhammad; Nasrullah, Nasrullah; Syafira, Defy (Department of Informatics Faculty of Engineering Universitas Malikussaleh, 2024)
Games are one of the entertainment media that people choose to relieve boredom or just to fill their free time. Apart from being an entertainment medium, games can also be a learning medium to improve a person's brain development. Action games provide a good opportunity to train children's agility in thinking. Action games are games with the main feature of rapid shooting facilities with lots of action where players must have fast reaction skills to avoid enemy fire or avoid obstacles. Most of the action games